2019
DOI: 10.1126/sciadv.aav3478
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating surface magnetic order in iron telluride

Abstract: Control of emergent magnetic orders in correlated electron materials promises new opportunities for applications in spintronics. For their technological exploitation, it is important to understand the role of surfaces and interfaces to other materials and their impact on the emergent magnetic orders. Here, we demonstrate for iron telluride, the nonsuperconducting parent compound of the iron chalcogenide superconductors, determination and manipulation of the surface magnetic structure by low-temperature spin-po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 37 publications
7
18
0
Order By: Relevance
“…This work has demonstrated that the surface magnetic structure faithfully follows the bulk magnetic phase diagram as a function of interstitial iron in terms of both the crystallographic and magnetic structures giving consistent results with neutron scattering on the interstitial iron concentration where the magnetic and crystallographic structures change. However, an important difference was observed for the magnetic structure in the collinear "double-stripe" phase for small values of x. Tunneling measurements show a periodicity consistent with the stripe phase reported based on neutron scattering [58], however recent measurements in vector magnetic fields have observed a significant out-of-plane canting along the crystallographic c-axis of the magnetic moment of θ ∼ 28 • where neutron scattering reports the moments to be entirely in the ab plane (θ = 0) [59,60]. Interestingly, such a magnetic structure is consistent with early studies on Fe 1.12 Te [61]; however, given more recent work, it is possible that this concentration was at the boundary between collinear and helical magnetism possibly complicating the interpretation.…”
Section: Introductionsupporting
confidence: 68%
“…This work has demonstrated that the surface magnetic structure faithfully follows the bulk magnetic phase diagram as a function of interstitial iron in terms of both the crystallographic and magnetic structures giving consistent results with neutron scattering on the interstitial iron concentration where the magnetic and crystallographic structures change. However, an important difference was observed for the magnetic structure in the collinear "double-stripe" phase for small values of x. Tunneling measurements show a periodicity consistent with the stripe phase reported based on neutron scattering [58], however recent measurements in vector magnetic fields have observed a significant out-of-plane canting along the crystallographic c-axis of the magnetic moment of θ ∼ 28 • where neutron scattering reports the moments to be entirely in the ab plane (θ = 0) [59,60]. Interestingly, such a magnetic structure is consistent with early studies on Fe 1.12 Te [61]; however, given more recent work, it is possible that this concentration was at the boundary between collinear and helical magnetism possibly complicating the interpretation.…”
Section: Introductionsupporting
confidence: 68%
“…We note that a very similar checkerboard-like AFM order shows up at the surface of samples with much higher levels of excess Fe doping ( x ≈ 0.2), where the bulk crystal structure is orthorhombic. 6 Based on the above observations, we deduce that a noticeable amount of strain is already present in the sample.…”
Section: Resultsmentioning
confidence: 62%
“… 1 , 2 Most of them exhibit a (π, π)-ordered magnetic phase in some part of the phase diagram which is suppressed by chemical substitution until superconductivity sets in. This general behavior hints to the importance of magnetic fluctuations for superconductivity; 3 yet, it is disrupted by the iron chalcogenides where the magnetic order occurs in the (π, 0) direction in Fe 1+ x Te 4 6 and nematicity in the superconducting FeSe occurs without magnetic order, 7 , 8 whereas in the pnictides nematicity and magnetic order are intimately linked and the magnetic order occurs at the same (π, π) scattering vector at which magnetic fluctuations dominate in the superconducting state. The difference in the magnetic order is also reflected in a different crystal structure in Fe 1+ x Te.…”
mentioning
confidence: 96%
See 2 more Smart Citations